A case report of an STEMI mimicker in a patient presenting with haemoptysis and chest pain with metastatic myocardial infiltration and left ventricular mural thrombi. Issue 2 (5th January 2021) - Zhou, Ruihai; Prasada, Sudhir; Roth, Michael
Abstract: Background : ST-elevation myocardial infarction (STEMI) requires timely coronary reperfusion but localizing ST-segment elevation (STE) can develop in clinical settings other than STEMI. Case summary : We report a case of a 66-year-old man, with a history of diabetes mellitus and arthritis presenting with haemoptysis and chest pain. The electrocardiogram (ECG) at presentation showed marked localizing STE but emergent cardiac catheterization showed no significant coronary artery obstruction and the serial serum cardiac troponin levels were within normal limits. The patient was found to have squamous cell carcinoma with a right upper lobe cavitated lung mass and cardiac infiltrative metastasis as shown by computed tomography, echocardiography, cardiac magnetic resonance, and 18F-fluorodeoxyglucose - positron emission tomography-computed tomography (FDG-PET-CT) imaging. Mobile left ventricular mural thrombi were also noted on echocardiography. Discussion : Metastatic myocardial infiltration can cause STE mimicking STEMI on ECG. The STE is persistent and may reflect an ongoing injury current between the infiltrated and normal myocardium. The STE is localizing, which may have value in evaluating the extent and region of metastatic myocardial damage. Myocardial metastasis can be complicated by ventricular mural thrombosis and due to lack of population data, there is no firm guidance on choice of anticoagulation.